Analisis Kesesuaian Kualitas Pasar SNI 8152 Pasar Rakyat Pada 3 Pasar Di Kutai Kartanegara - Heru Suprapto; Ince Raden (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2022)
This study examines the description of the suitability of SNI 8152 in 3 traditional markets, namely the Loa Kulu market, Sanga-Sanga market and Kuala Samboja market. The focus of the study is to analyze the level of conformity of the General Requirements, Technical Requirements and Management Requirements of the people's market with SNI. None of the three markets have conformity with SNI 8152, because the person in charge of the traditional market standards is the responsibility of the regional apparatus (PD). Lack of coordination between PDs, among others, that the Department of Industry and Trade manages uses the trade facilities after the building is handed over from the Department of Public Works, where the technical requirements for trade facilities and infrastructure do not meet the expectations of the Department of Industry and Trade.